Using Evidence-Based Design to Improve Pharmacy Department Efficiency. (October 2016) - Greenroyd, Fraser L.; Hayward, Rebecca; Price, Andrew; Demian, Peter; Sharma, Shrikant
Using a case study of a pharmacy department rebuild in the South West of England, this article examines the use of evidence-based design to improve the efficiency and staff well-being with a new design. This article compares three designs, the current design, an anecdotal design, and an evidence-based design, to identify how evidence-based design can improve efficiency and staff well-being by reducing walking time and distance. Data were collected from the existing building and used to measure the efficiency of the department in its current state. These data were then mapped onto an anecdotal design, produced by architects from interviews and workshops with the end users, and an evidence-based design, produced by highlighting functions with high adjacencies. This changed the view on the working processes within the department, shifting away from a focus on the existing robotic dispensing system. Using evidence-based design was found to decrease the walking time and distance for staff by 24%, as opposed to the anecdotal design, which increased these parameters by 9%, and is predicted to save the department 248 min across 2 days in staff time spent walking.